PENGARUH KOMBINASI JARAK TANAM DAN UMUR BIBIT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica campestris L.) - Alfandi Alfandi; Dodi Budirahman; Zaenal Hasikin (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2017)
This study aims to determine: (1) the real influence between treatment of spacing and age of seedlings on growth and yield of pakcoy plants (Brassica campestris L.), (2) the best spacing and age of seedlings on growth and yield of pakcoy plants (Brassica campestris L.), and (3) the relationship between growth components and net weight per plot of pakcoy plants (Brassica campestris L.). The study was conducted in Pasir Agung Village, Hantara Subdistrict, Kuningan Regency, West Java, from January 2014 to March 2014. The method used in this study was the experimental method. The experimental design used was Randomized Block Design (RBD). ) This experiment consisted of 9 combinations of treatment spacing and age of seedlings, each repeated three times, so that there were 27 experimental plots. The combination of treatments tested in the field are: A (10 cm x 20 cm and 10 days after seeding (HSS)), B (10 cm x 20 cm and 14 HSS), C (10 cm x 20 cm and 21 HSS), D (10 cm x 15 cm and 10 HSS), E (10 cm x 15 cm and 14 HSS), F (10 cm x 15 cm and 18 HSS), G (10 cm x 20 cm and 10 HSS), H (10 cm x 20 cm and 14 HSS), and I (10 cm x 20 cm and 18 HSS). The results showed that: (1) there was a significant effect between spacing and age of seedlings on average plant heights of 7, 14, and 21 HST, number of leaves aged 7 and 21 HST, root voium, weight of biomass per plant and per plot, and net weight per plant and per plot, (2) the highest net weight per plot is found in treatment E (spacing of 10 cm x 15 cm and age of seedlings of 14 HSS) with weights of 5.36 kg / plot or equivalent with 14.29 tons / ha, but not significantly different from treatment F (spacing of 10 cm x 15 cm and age of 18 HSS seedlings) and treatment I (spacing of 10 cm x 10 cm and age of 18 HSS seedlings), (3) there is a significant correlation between plant height aged 7 and 21 HST and the number of leaves aged 7 HST with net weights per plot.